Pengetahuan Perpajakan, Kepatuhan Wajib Pajak dan Kesadaran Wajib Pajak Sebagai Pemediasi - Septyana, Sarah; Anggiriawan, Putu Budi; Yudha, Cokorda Krisna (E-Jurnal Akuntansi, 2022)
The research aims to determine the effect of knowledge of taxation on taxpayer compliance with taxpayer awareness as a mediating variable. The analysis technique used is path analysis using SPSS software. The research population was individual taxpayers registered at North Badung KPP Pratama totaling 101,577 taxpayers and 100 people as a sample. The sampling method is using the nonprobability sampling method. Data collection method by distributing questionnaires to 100 individual taxpayers. The results of the study stated that knowledge of taxation had an effect on taxpayer awareness, taxpayer awareness had an effect on taxpayer compliance, and knowledge of taxation had had an effect on taxpayer compliance, while taxpayer awareness could not mediate the influence of tax knowledge on taxpayer compliance. Keywords: Tax Knowledge; Taxpayer Compliance; Taxpayer Awareness.